2006
DOI: 10.1074/jbc.m603656200
|View full text |Cite
|
Sign up to set email alerts
|

Protective Mechanisms against Homocysteine Toxicity

Abstract: Homocysteine (Hcy) editing by methionyl-tRNA synthetase results in the formation of Hcy-thiolactone and initiates a pathway that has been implicated in human disease. In addition to being cleared from the circulation by urinary excretion, Hcythiolactone is detoxified by the serum Hcy-thiolactonase/paraoxonase carried on high density lipoprotein. Whether Hcy-thiolactone is detoxified inside cells was unknown. Here we show that Hcy-thiolactone is hydrolyzed by an intracellular enzyme, which we have purified to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 41 publications
3
82
0
Order By: Relevance
“…However, this function has remained enigmatic for many years. Recently, BH was shown to be involved in the post-translational processing of peptides for antigen presentation (36) and a protective mechanism against homocysteine toxicity (37). Furthermore, BH has been shown to interact with several proteins, such as cAMP-binding ectoprotein in yeast (38), the human homologue of ubiquitin-conjugating enzyme 9 (39), human ribosomal proteins (40), and amyloid precursor protein (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, this function has remained enigmatic for many years. Recently, BH was shown to be involved in the post-translational processing of peptides for antigen presentation (36) and a protective mechanism against homocysteine toxicity (37). Furthermore, BH has been shown to interact with several proteins, such as cAMP-binding ectoprotein in yeast (38), the human homologue of ubiquitin-conjugating enzyme 9 (39), human ribosomal proteins (40), and amyloid precursor protein (41).…”
Section: Discussionmentioning
confidence: 99%
“…BH exhibits mainly broad specificity aminopeptidase activity, with citrulline being the most effective substrate (12,14). It is involved in homocysteinethiolactone metabolism (17), antigen presentation (18,19), and amyloid-␤-peptide clearance (20,21). Interestingly, BH knockout mouse shows analogous phenotypes to those of filaggrindeficient flaky tail ft/ft mouse, including ichthyosis and atopylike phenotype and tail constriction (22)(23)(24).…”
mentioning
confidence: 99%
“…Numerous cellular functions other than bleomycin detoxification have been described for yeast Lap3p and its orthologs (Koldamova et al, 1998;Montoya et al, 1998;Zimny et al, 2006;Montoya et al, 2007;Kamata et al, 2011) Furthermore, cysteine proteases throughout nature have demonstrated a role in a large variety of processes, ranging from signaling pathways in many organisms to programmed cell death (Degterev et al, 2003). Our results presented here raise further questions regarding the nature of the function of the Candida protein.…”
Section: Discussionmentioning
confidence: 68%
“…Although GAL6 deletion mutants are viable, Gal6p (Lap3p) is known to exert a modest negative effect on GAL promoter mediated transcription (Zheng et al, 1997). In humans, BLH1 is expressed in most tissue types (Takeda et al, 1996), and functions in protection against homocysteine toxicity (Zimny et al, 2006) and progression of atopic dermatitis. A correlative association with development of astrogliosis has also been attributed to abnormalities in BLH1 function (Montoya et al, 1998;Montoya et al, 2007).…”
Section: Introductionmentioning
confidence: 99%